RELATIONSHIP BETWEEN INTERPERSONAL COMMUNICATION ABILITY AND LEARNING ENVIRONMENT WITH STUDENTS MATHEMATICS LEARNING OUTCOMES OF CLASS XI IPA - Moga Wiraningrum; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Learning outcomes is the accomplishment of the learning process. Low mathematics outcomes are influenced by factors that come from within or outside the students’ self. For example, a low ability of interpersonal communication makes the interaction of students with other people uncomfortable, and a less conducive learning environment can reduce the concentration of students during the learning process. The study aims to determine the relationship between the ability of interpersonal communication and learning environment with mathematics learning outcomes in student class XI Science (IPA), even semester of State Senior High School 9 Yogyakarta (SMA Negeri 9 Yogyakarta) in the academic year of 2016/2017. The population in this research was the students of class XI IPA, even semester of SMA Negeri 9 Yogyakarta in the academic year of 2016/2017, which consists of 5 classes with some 148 students. Samples were taken with a random sampling technique and derived class XI IPA 5 as a sample class with 28 students.  Data collection techniques use a questionnaire method to collect data on the ability of interpersonal communication and learning environment and test method mathematics achievement test. Test instruments used for validity and reliability. Test requirements analysis was a normality test, a test of independence, and a linearity test. Analysis of the data for testing hypotheses used linear regression analysis and correlation analysis. The results showed a positive and significant relationship between the ability of interpersonal communication and learning environment with mathematics learning outcomes in student class XI IPA even semester of SMA Negeri 9 Yogyakarta in the academic year of 2016/2017. It is showed by Fcount  Ftable is 7,6180 > 3,39 with  R = 0,6154 and R2 = 0,3787 with Ŷ = -71,6983 + 0,7204X1 + 0,9477X2 with RC =  and RC =  with EC =  and EC = .